Implementasi Nilai Toleransi Dalam Pernikahan Beda Agama - Fuji Astuti, Rahayu; widya, Ade (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
The attitude of tolerance in interfaith marriages is very important in nature to maintain family unity and harmony.Mutual respect and respect for religious differences in the family can build peace.This study aims to find out the components that cause religious differences in the family, to understand how tolerance can be implemented in children who are raised in families with different beliefs, and to understand how the social sees religious differences in the family. This research uses a qualitative descriptive approach, which means describing events explicitly in the form of implementing and accepting different religious families through interviews. Where data analysis is used using the inductive method. inductive method is a method of thinking or reasoning that starts from observations or specific data data to then draw general conclusions or theories. The results of the study concluded that families can be of different religions due to two things, namely marriage and conversion.The value of tolerance in question leads to attitudes and principles that allow a person to be open, appreciate, understand, and accept differences between other people and groups, regardless of religion, culture, ethnicity, opinion, or other factors.Tolerance towards society includes tolerance towards families of different religions, which includes religious freedom, respect for religious differences, and approval of religious differences.This attitude of tolerance applies to all types of applications carried out by the people in it.